Effect of COX-2 inhibitor meloxicam against traumatic brain injury-induced biochemical, histopathological changes and blood-brain barrier permeability - (:unkn) unknown (MANEY PUBLISHING, 2010)
Objective: The overproduction of reactive oxygen species and resultant damage to cellular proteins or lipids of cell membranes and DNA by free radicals are the underlying mechanisms of many neuropathologies. Cyclooxygenase-2 (COX-2) inhibitors have been suggested to be neuroprotective by reducing prostanoid and free radical synthesis, or by directing arachidonic acid metabolism through alternate pathways. This study investigated the putative neuroprotective effect of the COX-2 inhibitor, meloxicam, in a rat model of diffuse brain injury. Methods: Sprague-Dawley rats were subjected to traumatic brain injury with a weight-drop device using 300 g 21 m weight-height impact. The groups were: control, meloxicam (2 mg/kg, i.p.), trauma and trauma z meloxicam (2 mg/kg, i.p.). Forty-eight hours after the injury, neurological examination scores were measured, the animals were decapitated and brain tissues were taken. Brain edema and blood-brain barrier (BBB) permeability were evaluated by wet-dry weight method and Evans blue (EB) extravasation respectively. In brain tissues, malonedialdehyde, glutathione, myeloperoxidase and Na/K-ATPase levels were measured. Results: The neurological examination scores mildly increased in trauma groups 48 hours after the induction of trauma. Meloxicam treatment improved the altered neurological status. The trauma caused a significant increase in brain water content that was partially reversed by meloxicam. Meloxicam also reduced the EB extravasation indicating the preservation of the BBB integrity. Meloxicam treatment also significantly reduced the increase in malondialdehyde and myeloperoxidase levels glutathione content of the brains that had been significantly increased after trauma. Conclusion: Meloxicam exerts neuroprotective effect by preserving BBB permeability and by reducing brain edema (probably by its anti-inflammatory properties) in the diffuse brain injury model.
Keywords: Antioxidant; blood-brain barrier; brain injury; closed head trauma; edema; meloxicam; OXIDATIVE STRESS; HEAD-INJURY; RAT; CYCLOOXYGENASE-2; MODEL; INFLAMMATION; NEUROPROTECTION; METABOLISM; MODULATION; RELEASE